TESTING THE DEVELOPMENTAL ABILITY OF LEADER’S EMOTIONAL INTELLIGENCE WITH AGE ON ESCI - Rodrigues, Saritha Alfrida; Madgaonkar, Jyoti S. (European Scientific Journal, ESJ, 2013)
This study examined the developmental ability of emotional intelligence with age using ESCI, a reconceptualized measure of ECI 2 thru an upward feedback method. The sample included leaders (n=500) between the age range of 24-62 years belonging to various IT and manufacturing companies of India and their raters were direct reports (n=1500) between the age range of 19-62 years. The study finds that, EI of leaders (as perceived by self and others) consistently increases with age (from 24 to 45 years) but after reaching its peak at 45 years it declines in the fifth and sixth decade of life due to the decline in the Self-awareness competencies among older leader’s. The agreement in self-others ratings proved to be a better predictor of rater accuracy in evaluating leader’s EI on ESCI.